Clinical and Radioraphic Study to Investigate the Effect of Platelet-rich Fibrin Membranes (PRF) Application in Iatrogenic Exposure of the Dental Pulp: (Journal of Hama University, 2020)
Aim: The aim of this study was to evaluate the effect of platelet-rich fibrin (PRF) membranes in iatrogenic exposure of the dental pulp as a partial pulpotomy agent in permenant teeth. Material and Methods: In this study, 20 permenant teeth from 20 healthy patients aged 12-18 years with exposed pulps were randomly divided into two groups. 1) Experimental group (n=10): after removal of 1-2 mm of pulp and hemostasis, exposed pulp was covered with PRF membrane then a layer of mineral trioxide aggregate cement (MTA) was applied. 2) control group (n=10): after removal of 1-2 mm of pulp and hemostasis, the exposed pulp was covered with MTA. All teeth were restored with glass - ionomer cement and composite resin. Clinical and radioraphic evaluation was undertaken at (3, 6, and 12) months intervals. The results were analyzed using appropriate statistical tests.Results: All teeth responded positively to pulp sensibility tests, and radiographic examination revealed dentinal bridge formation and absence of periapical pathosis in both groups during follow-up periods.Conclusion: Clinical and radiological findings showed that the possibility of PRF membrane for partial pulpotomy in cases of iatrogenic exposure of the dental pulp because of its active bio-structure, which could open up future perspectives in maintaining the vitality of the dental pulp.